Tim-1 mucin domain-mutant mice display exacerbated atherosclerosis. (July 2022) - Douna, Hidde; Smit, Virginia; van Puijvelde, Gijs H.M.; Kiss, Mate G.; Binder, Christoph J.; Bot, llze; Kuchroo, Vijay K.; Lichtman, Andrew H.; Kuiper, Johan; Foks, Amanda C.
Abstract: Background and aims: Increasing evidence has shown that immune checkpoint molecules of the T-cell immunoglobulin and mucin domain (Tim) family are associated with diverse physiologic and pathologic processes. Previous studies of the role of Tim-1 in atherosclerosis using anti-Tim-1 antibodies have yielded contradictory results. We thus aimed to investigate atherosclerosis development in Tim-1 deficient mice. Methods: Mice with a specific loss of the Tim-1 mucin-domain ( Tim-1 Δmucin ) and C57BL/6 (WT) mice received a single injection of a recombinant adeno-associated virus encoding murine Pcsk9 (rAAV2/8-D377Y-mPcsk9) and were fed a Western type diet for 13 weeks to introduce atherosclerosis. Results: Tim-1 Δmucin mice developed significantly larger lesions in the aortic root compared to WT mice, with significantly more macrophages and a trend towards a larger necrotic core. Furthermore, Tim-1 Δmucin mice showed a significant loss of IL-10 + B cells and regulatory B cell subsets and increased pro-atherogenic splenic follicular B cells compared to WT mice. Moreover, Tim-1 Δmucin mice displayed a dramatic reduction in Th2-associated immune response compared to controls but we did not observe any changes in humoral immunity. Conclusions: In summary, Tim-1 Δmucin mice displayed a profound impairment in IL-10 + B cells and an imbalance in the Th1/Th2 ratio, which associated with exacerbated atherosclerosis. Graphical abstract: Image 1 Highlights: TIm-1 deficient mice show exacerbated atherosclerosis. Regulatory IL-10 + B cells are reduced in atherosclerotic TIm-1 deficient mice. Atherosclerotic TIm-1 deficient mice show increased follicular B cells and an imbalanced Th1/Th2 ratio. Despite reduced Th2-associated immunity, humoral responses are unaffected.